Prevalance of Gastrointestinal Protozoa of Cats in Animal Hospital and Animal Clinic in Surabaya - Amara Lintang Pagati; Lucia Tri Suwanti; Chairul Anwar Nidom; Wiwik Misaco Yuniarti; Sarmanu Sarmanu; Endang Suprihati (Journal of Parasite Science (JoPS), 2018)
Research of gastrointestinal protozoan in cats at Surabaya are still limited. Protozoa infection of the gastrointestinal tract can cause diarrhea and even zoonosis. This research aimed to identify and determine the prevalence of protozoan in cats in animal hostptal and animal clinic in Surabaya. Ninety  fecal samples were collected from 2 animal clinic and one animal hospital. Samples were  examined e wet mount (native, sedimentation, and floatation) and (Ziehl Nellsen) stain. Protozoa was identified by using a light microscope with 400x and 1000x magnification. The result showed 68,89% of samples were positively infected by gastrointestinal protozoa. The protozoa were Blastocystis sp, Cryptosporidium sp, Giardia sp, and Eimeria sp. By chi square test, there was  not significant differences the prevalence of gastrointestinal protozoan in cat between sex, age, breed, and diarrhea status